Quantitative Simulation of the Coremas-Mãe D'Água Water System Located in Brazil’s Hinterland Using ACQUANET Model - Vieira, Allan Sarmento; de Amorin, Luana Andrade; Fontgalland, Isabel (Technium Social Sciences Journal, 2023)
The main objective of this research is to analyze quantitatively the water situation of the Coremas water system considering the last water crisis that began in 2012, located in the hydrographic basin of the rivers Piancó-Piranhas-Açu, Brazil, using the ACQUANET simulation model. A series of inflows was also constructed using the rainfall-runoff model Soil Moisture Accounting Procedure. Analyzing the results obtained for the simulated time horizon of the two reservoirs, the efficiency of meeting demands in the simulation of scenario 1, which evaluated the two reservoirs individually, some failures were observed in the sectors of human supply, irrigation, industry and pisciculture, where they presented guarantees above 95%. In the simulation of scenario 2, which was considered in the analysis as a single reservoir, both in the rainy and dry periods, all demands related to the system, such as human supply, animal feeding, irrigation, industry and fish farming, had 100% reliability. Therefore, the Coremas system, despite the water crisis experienced, is considered sustainable and can be used to transfer water to other hydrographic basins during the water crisis period.